2018
DOI: 10.1073/pnas.1712625115
|View full text |Cite
|
Sign up to set email alerts
|

Elevated d -2-hydroxyglutarate during colitis drives progression to colorectal cancer

Abstract: SignificanceHere, we identify a role for D2HG in the progression of colitis to colon cancer. In a mouse model of colitis-associated colon cancer (CAC), urine D2HG level during colitis correlates positively with severity of tumorigenesis. Elevated D2HG enhances CAC in mice and confers a hyperproliferative, nonapoptotic phenotype in cultured intestinal epithelial cells prone to neoplastic progression in the setting of chronic inflammation. Hif-1α is a key regulator of D2HGDH transcription, an enzyme that elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 34 publications
(56 reference statements)
2
37
0
Order By: Relevance
“…D2HGDH transcriptional regulation studies in colorectal cancer have recently been reported (Han et al, ). These investigators identified a putative Hif‐1α transcription factor binding site in the D2HGDH promoter, suggesting that Hif‐1α controls both the expression of D‐2‐HGDH as well as D‐2‐HG levels.…”
Section: Discussionmentioning
confidence: 99%
“…D2HGDH transcriptional regulation studies in colorectal cancer have recently been reported (Han et al, ). These investigators identified a putative Hif‐1α transcription factor binding site in the D2HGDH promoter, suggesting that Hif‐1α controls both the expression of D‐2‐HGDH as well as D‐2‐HG levels.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, D‐2‐HG is involved in epigenetic alteration (Sciacovelli & Frezza, ; Dang & Su, ; Janke, Iavarone, & Rine, ), dysregulation of ROS production and stabilization of HIF‐1 (Collins et al , ), inhibition of α‐ketoglutarate‐dependent and non‐heme iron‐dependent dioxygenases, including members of the alkylated DNA repair protein (AlkB) family, such as ALKBH2 and ALKBH3 (Chen et al , ), metabolic dysregulation and impairment of cell differentiation (Bezawork‐Geleta et al , ; Dang & Su, ) and avoidance of the immune system (Lucca & Hafler, ). Furthermore, a recent report suggests that 2‐HG can also be involved in the progression from colitis to colon cancer, and the detection of this oncometabolite in the urine can be considered a valuable diagnostic tool to identify patients at risk for cancer development (Han et al , ).…”
Section: Oncometabolites and Their Related Metabolic Enzymesmentioning
confidence: 99%
“…HIF-1α associates with hypoxia response element (HRE), forming the response element binding protein and activating the formation of complexes of other transcription factors. HIF-1α has been revealed to upregulate expression of VEGF and bFGF (24,25), and upregulation of HIF-1α in CRC tissues during hypoxic conditions enabled the survival of tumor cells and potentiated evolution of tumors (26,27). Proliferation of endothelial cells underlies the formation of blood vessels and thus is required for angiogenesis, both physiologically and pathophysiologically in tumor tissues.…”
Section: Discussionmentioning
confidence: 99%